Dicarbonyl(η(5)-cyclopentadienyl)[2-(phenylsulfanyl)ethyl]iron(II) - Mkhize, Dennis S. (International Union of Crystallography, 2011)
The title compound, [Fe(C(5)H(5))(C(8)H(9)S)(CO)(2)], is a three-legged piano-stool iron(II) complex that is characterized by a thioethyl-linked phenyl ring and a cyclopentadienyl moiety that occupies the apical coordination site. The two aromatic rings are essentially planar with the same maximum deviation of 0.009 Å. The mean planes of the phenyl and cyclopentadienyl rings bisect at an acute angle of 50.08°.